Phenotypic and genotypic diversity of yeast isolated from cancer patients and their environment and their antifungal sensitivity pattern - ZAHRAA DAWOOD GATEA AL-DARRAJI; MOHANAD KHALAF MOHAMMED-AMEEN (Society for Indonesian Biodiversity, 2023)
Abstract. Al-Darraji ZDG, Mohammed-Ameen MKM. 2023. Phenotypic and genotypic diversity of yeast isolated from cancer patients and their environment and their antifungal sensitivity pattern. Biodiversitas 24: 4166-4174. This study aimed to investigate yeast diversity and their antifungal susceptibility patterns in 853 samples collected from cancer patients, their apparently healthy companions, their beds, their tables, and indoor hospital air. The samples were cultured and identified using classical phenotypic characteristics and a molecular method utilizing amplification of ITS conservative regions of rRNA. The sum of phenotyping and genotyping identification revealed that 102 yeast isolates included 6 genera and 14 species. Candida sp. was the most dominant genera (84.31%), followed by Naganishia sp. (10.78%). Candida albicans (24.50%) and C. krusei (16.66%) were the most prevalent yeast species. Fluconazole, caspofungin, and voriconazole exhibited potent antifungal activities against the most yeast species with low minimum inhibitory concentration (MIC) values compared with high MIC (64 µg/mL) values against Meyerozyma guilliermondi, Naganishia difflunes, and C. tropicalis. To conclude, the antifungal activity was isolate- and species-specific and the higher antifungal concentrations led to a more-rapid expression of activity. The high isolation rate of yeasts from beds and tables, advocated the use of various monitoring systems to ensure thorough cleaning and consistent disinfection of surfaces around patients and health care providers. The study findings showed that the molecular method was superior to the phenotyping technique in identifying yeast isolates. While similar research has been performed in different locations, the current project represents a unique milestone for this particular institution, and offers an opportunity to advance research in this area.